Supporting People with Social Care Needs On Release from Prison: A Scoping Review - Sue Tucker; Deborah Buck; Amy Roberts; Claire Hargreaves (Journal of Long-Term Care, 2024)
Context: Social care need in prisons is increasing in many countries. However, the delivery of social care in prisons has been (at best) inconsistent and there has been no previous review to inform provision for people on release.